2018
DOI: 10.1016/j.ijsu.2018.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical outcomes after anterior cruciate ligament reconstruction with hamstring tendon autograft versus soft-tissue allograft: A meta-analysis of randomised controlled trials

Abstract: Soft-tissue allografts are inferior to hamstring tendon autografts with respect to subjective patient evaluation and knee stability but superior in the complication of hypoesthesia for patients undergoing primary ACL reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Although the literature on SCR with fascia lata is limited, the healing rate of autografts seems to be far better. The same is known for anterior cruciate ligament reconstruction where the use of allografts is known to be safe, but can be associated with a significantly higher failure and reoperation rate and postoperative stability [2,9,31]. Allograft incorporation to host tissue, which can be up to 1 year, takes much longer compared with autografts [5].…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature on SCR with fascia lata is limited, the healing rate of autografts seems to be far better. The same is known for anterior cruciate ligament reconstruction where the use of allografts is known to be safe, but can be associated with a significantly higher failure and reoperation rate and postoperative stability [2,9,31]. Allograft incorporation to host tissue, which can be up to 1 year, takes much longer compared with autografts [5].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the meta-analysis found statistically significant difference in subjective IKDC, with a mean difference of 2.43 to the detriment of allografts (95% CI 0.69-4.18; P ¼ .006) and a marginal mean difference in Tegner score (mean difference 0.24; 95% CI 0.03-0.45; P ¼ .03) as well as in side-to-side differences (mean difference À1.37; 95% CI À2.44 to 0.30; P ¼ .01). Wang et al 36 did not find significant differences between groups when comparing the Lysholm score, complications, pivot shift test, anterior drawer test, Lachman test, overall IKDC score, or range of motion. Based on their findings, the authors concluded that soft-tissue allografts are inferior to hamstring tendon autografts with respect to subjective patient evaluation and knee stability but superior in the complication of hypoesthesia for patients undergoing ACLR.…”
Section: Discussionmentioning
confidence: 93%
“…Based on their findings, the authors concluded that soft-tissue allografts are inferior to hamstring tendon autografts with respect to subjective patient evaluation and knee stability but superior in the complication of hypoesthesia for patients undergoing ACLR. 36 Yet, some shortcomings must be noted hereby. First, it is questionable as to whether these differences are actually outside the noninferiority margin, that is, as to whether the aforementioned differences within effectiveness outcomes are clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Only one of the seven studies included in this systematic review has reported complications related to the harvesting of autografts, which was pain at the donor site following gracilis tendon harvesting (18). However, this may be an underrepresentation of hamstring harvest donor site morbidity, given that larger series involving anterior cruciate ligament reconstructions have reported a higher incidence of donor site morbidity, such as saphenous nerve injury, weakness of knee flexion, and hypoesthesia (42,43). For other autografts such as ITB, Philippon et al (44) pointed out that infection, pain, and muscular hernia are potential complications.…”
Section: Discussionmentioning
confidence: 99%